Restoration of Mitochondrial Dysfunction in 6-Hydroxydopamine Induced Parkinson's disease: a Complete Review - Sidharth Mehan; Gurpreet Kaur; Rajesh Dudi; Manju Rajput; Sanjeev Kalra (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2017)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by neuronal cell death in the specific brain region like basal ganglia, cerebral cortex and hippocampus. Symptoms associated with PD patients are rigidity, akathesia, tremor, postural imbalance, cognitive and memory dysfunctions. Pathological hallmarks are dopaminergic neuronal degeneration, neuro-inflammation, oxidative stress, free radical generation. In the typical Parkinson's disease model, 6-Hydroxydopamine (6-OHDA) is delivered unilaterally by stereotactic injection into the SNc (substantia nigra pars-compacta) or the striatum mimics the PD symptoms. In addition, it has been shown that 6-OHDA is toxic to complex I & IV of the mitochondrial respiratory chain, leading to subsequent respiratory inhibition and further processed ATP depletion, oxidative stress and neuro-infl ammation. Forskolin (FSK), a diterpene natural plant phytochemical obtained from (Coleus Forskohli), a potent direct activator of adenyl cyclase (AC) enzyme which further activates cAMP/PKA/CREB pathway. FSK mediated activation of AC/cAMP/PKA/CREB pathway is responsible for various neuroprotective mechanisms Based on important and versatile role of FSK, the present study has been designed to investigate the role of cAMP mediated CREB activation in 6-hydroxydopamine induced mitochondrial associated neurotoxicity in rats. Further the studies are extended to understand the disease pathogenesis and to investigate and discuss the various possible central mechanisms involved in the effect of such targets using behavioral paradigm and biochemical markers of neurodegeneration.